OPTIMALISASI PENGEMBANGAN DAYA TARIK WISATA (STUDI KASUS:KAMPUNG WISATA TUAN KENTANG PALEMBANG) - Kaiman Kaiman; Elly Malihah; Rini Andari (Politeknik Pariwisata Palembang, 2026)
Rural tourism is a tourism activity where the tourist experience is related to various nature-based activities, agriculture, and lifestyle in the countryside. South Sumatra itself has at least 123 tourist villages spread across several districts and cities. There are many potential tourist villages in the city of Palembang, one of which is the tuan kentang village. Tuan kentang village is located on Jl. Aiptu a wahab kec. Seberang Ulu I kota Palembang.Tuan kentang is known as the